Effect of nutrient enrichment on δ13CH4 and the methane production pathway in the Florida Everglades. Issue 7 (28th October 2013) - Holmes, M. Elizabeth; Chanton, Jeffrey P.; Bae, Hee‐Sung; Ogram, Andrew
Abstract Water Conservation Area 2A in the Florida Everglades is characterized by a nutrient gradient with high levels in the north from agricultural runoff and more oligotrophic conditions in the southern interior. Based on laboratory incubations and field studies, we found that the relative importance of methane (CH4) production mechanisms shifted along this gradient, with a greater contribution due to hydrogenotrophic methanogenesis at higher nutrient levels. The relative contributions of hydrogenotrophic and acetoclastic methanogenesis were determined from laboratory experiments and verified with field results. In the lab the relative contributions of the two pathways were determined from the differences in CH4 production rates in soil collected from sites along the nutrient gradient that was incubated with and without an inhibitor of acetoclastic methanogenesis (methyl fluoride, CH3F). In the nutrient‐poor soil, most of the CH4 was formed via acetate fermentation and only 25% came from hydrogenotrophic methanogenesis. At the nutrient‐impacted site CH4 was produced at fourfold higher rates and the proportion of CH4 produced via hydrogenotrophic methanogenesis increased to 50%. Isotopic fractionation factors for hydrogenotrophic and acetoclastic methanogenesis were calculated from the soil incubations and applied to δ13C‐CO2 and δ13C‐CH4 measured in pore water from the same transect. The trend of increased hydrogenotrophic relative to acetoclastic CH4 production along the nutrient‐impacted gradient was mirrored in the field data, which produced similar results to the lab incubation work, with up to 23% of the CH4 produced from hydrogenotrophic methanogenesis at the nutrient‐poor site and nearly half at the nutrient‐impacted site.